Correlation of Learning Interest with Student Learning Outcomes at SDIT Al-Muthmainnah - Mira Oktopiya; A.A. Musyaffa; Donal Saputra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study is based on the phenomenon of low student interest in learning, such as lack of attention to teachers' explanations and low involvement in tasks, which has an impact on student learning outcomes. Based on this, this study aims to analyze the relationship between learning interest and student learning outcomes in Pancasila Education at SDIT Al-Muthmainnah. The research method used is a quantitative approach with a correlational type with a population of all fourth grade b and c students at SDIT Al-Muthmainnah with a total of 48 students. The sampling technique used random sampling, which produced 43 respondents as research subjects. Data were collected through a learning interest questionnaire that had been tested for validity and reliability, as well as documentation of students' formative scores. Data analysis was performed using the Product Moment correlation test. The results showed a significant positive relationship between learning interest and student learning outcomes with a correlation coefficient of r = 0.403 > r table = 0.308 with a significance level of 0.004 < 0.05. Thus, it can be concluded that these values indicate a significant relationship between learning interest and learning outcomes, with the level of relationship falling into the moderate or sufficient category. Based on these findings, it can be concluded that interest in learning is an important psychological factor that contributes to students' academic achievement. Therefore, increasing interest in learning needs to be a focus for teachers in optimizing learning outcomes in Pancasila Education subjects.